Phraseme and the motivationality of its meaning - Křivancová, Michaela (Bohemistyka, 2020)
While exploring the motivationality of Czech phraseological units, this article focuses undivided attention on ‘the motivation of word collocations’ induced by the relation between individual components and the phraseological whole, paying no regard to motivation inspired by phonetics, word formation, or semasiology/onomasiology. It is generally acknowledged that, in most cases, phraseological units are not directly and measurably motivated by their components. Our aim is to evidence that direct motivation can be traced in some phraseological groupings performing the denominating function and in phrasemes comprising a particular formal structure which will be described and supported by examples.